Il concetto di sezione nel metodo compositivo di Aldo Rossi. - Casadei, Christian <1980> (Alma Mater Studiorum - Università di Bologna, 2010)
Purpose of this research is to deepen the study on the section in architecture. The survey aims as important elements in the project Teatro Domestico by Aldo Rossi built for the XVII Triennale di Milano in 1986 and, through the implementation on several topics of architecture, verify the timeliness and fertility in the new compositional exercises. Through the study of certain areas of the Rossi’s theory we tried to find a common thread for the reading of the theater project. The theater is the place of the ephemeral and the artificial, which is why his destiny is the end and the fatal loss. The design and construction of theater setting has always had a double meaning between the value of civil architecture and testing of new technologies available. Rossi's experience in this area are clear examples of the inseparable relationship between the representation of architecture as art and design of architecture as a model of reality. In the Teatro Domestico, the distinction between representation and the real world is constantly canceled and returned through the reversal of the meaning and through the skip of scale. At present, studies conducted on the work of Rossi concern the report that the architectural composition is the theory of form, focusing compositional development of a manufacturing process between the typological analysis and form invention. The research, through the analysis of some projects few designs, will try to analyze this issue through the rules of composition both graphical and concrete construction, hoping to decipher the mechanism underlying the invention. The almost total lack of published material on the project Teatro Domestico and the opportunity to visit the archives that preserve the drawings, has allowed the author of this study to deepen the internal issues in the project, thus placing this search as a first step toward possible further analysis on the works of Rossi linked to performance world. The final aim is therefore to produce material that can best describe the work of Rossi. Through the reading of the material published by the same author and the vision of unpublished material preserved in the archives, it was possible to develop new material and increasing knowledge about the work, otherwise difficult to analyze. The research is divided into two groups. The first, taking into account the close relationship most frequently mentioned by Rossi himself between archeology and architectural composition, stresses the importance of tipo such as urban composition reading system as well as open tool of invention. Resuming Ezio Bonfanti’s essay on the work of the architect we wanted to investigate how the paratactic method is applied to the early work conceived and, subsequently as the process reaches a complexity accentuated, while keeping stable the basic terms. Following a brief introduction related to the concept of the section and the different interpretations that over time the term had, we tried to identify with this facility a methodology for reading Rossi’s projects. The result is a constant typological interpretation of the term, not only related to the composition in plant but also through the elevation plans. The section is therefore intended as the overturning of such elevation is marked on the same plane of the terms used, there is a different approach, but a similarity of characters. The identification of architectural phonemes allows comparison with other arts. The research goes in the direction of language trying to identify the relationship between representation and construction, between the ephemeral and the real world. In this sense it will highlight the similarities between the graphic material produced by Ross and some important examples of contemporary author. The comparison between the composition system with the surrealist world of painting and literature will facilitate the understanding and identification of possible rules applied by Rossi. The second part of the research is characterized by a focus on the intent of the project chosen. Teatro Domestico embodies a number of elements that seem to conclude (assuming an end point but also to start) a curriculum author. With it, the experiments carried out on the theater started with the project for the Teatrino Scientifico (1978) through the project for the Teatro del Mondo (1979), into a Laic Tabernacle representative collective and private memory of the city. Starting from a reading of the draft, through the collection of published material, we’ve made an analysis on the explicit themes of the work, finding the conceptual references. Following the taking view of the original materials not published kept at Aldo Rossi's Archive Collection of the Canadian Center for Architecture in Montréal, will be implemented through the existing techniques for digital representation, a virtual reconstruction of the project, adding little to the material, a new element for future studies. The reconstruction is part of a larger research studies where the current technologies of composition and representation in architecture stand side by side with research on the method of composition of this architect. The results achieved are in addition to experiences in the past dealt with the reconstruction of some of the lost works of Aldo Rossi. A partial objective is to reactivate a discourse around this work is considered non-principal, among others born in the prolific activities. Reassessment of development projects which would bring the level of ephemeral works most frequented by giving them the value earned. In conclusion, the research aims to open a new field of interest on the part not only as a technical instrument of representation of an idea but as an actual mechanism through which composition is formed and the idea is developed.